2020
DOI: 10.3389/fmicb.2020.02094
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Survey of E. coli From the Bladders of Women With and Without Lower Urinary Tract Symptoms

Abstract: Urinary tract infections (UTIs) are one of the most common human bacterial infections. While UTIs are commonly associated with colonization by Escherichia coli , members of this species also have been found within the bladder of individuals with no lower urinary tract symptoms (no LUTS), also known as asymptomatic bacteriuria. Prior studies have found that both uropathogenic E. coli (UPEC) strains and E. coli isolates that are not associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 84 publications
10
44
0
1
Order By: Relevance
“…The protective role of particular strains belonging to Lactobacillus jensenii [24,25], can possibly contribute to the health maintenance of an individual with high abundance of Enterobacteriaceae, including an uropathogenic ST131 Escherichia coli (UPEC) according to its gene content [26] (unpublished data). This data also highlights the relevance of strain level characterization to understand FUM role in health and disease, as previously noticed [27,28].…”
Section: Discussionsupporting
confidence: 79%
“…The protective role of particular strains belonging to Lactobacillus jensenii [24,25], can possibly contribute to the health maintenance of an individual with high abundance of Enterobacteriaceae, including an uropathogenic ST131 Escherichia coli (UPEC) according to its gene content [26] (unpublished data). This data also highlights the relevance of strain level characterization to understand FUM role in health and disease, as previously noticed [27,28].…”
Section: Discussionsupporting
confidence: 79%
“…Mapping urine metagenome assemblies to a curated virulence factor database showed that UTI-causing strains were enriched in virulence factors (including iron uptake systems ( sit, chu, iro, ybt operons), colibactin ( clb ), and type 6 secretion systems) relative to an E. coli species-wide database, though many of these were also present in the one urine sample from a control participant for which we had sufficient coverage to assess gene content ( Methods , Table S8). This apparent transition of a likely urovirulent strain to the bladder of healthy women without eliciting UTI symptoms is consistent with previous studies which have been unable to identify genetic markers of urovirulence in mice 48 , or consistently discriminate between UTI and asymptomatic bacteriuria strains in women 50 . Nevertheless, the divergence in clinical outcomes after bacterial invasion of the bladder may still arise due to phenotypic differences in E. coli strains reaching the bladder that are not readily apparent in genome comparisons.…”
Section: Resultssupporting
confidence: 91%
“…Only some differences in motility genes between isolates from UTI patients and healthy individuals were found. Therefore, E. coli is part of the commensal urinary microbiota and other aspects may be determining its involvement in the development of urinary tract symptoms ( Garretto et al., 2020 ). Moreover, Escherichia coli has a greater pathogenicity in polymicrobial infections, mainly when it is isolated together with Enterococcus , although the mechanisms underlying this coinfection are not well understood ( Lavigne et al., 2008 ; Croxall et al., 2011 ).…”
Section: Influence Of the Urinary Microbiome On Diseasementioning
confidence: 99%